Overcoming constraints to immigrant entrepreneurship in Croatia: the role of formal and informal institutions. Issue 8 (17th November 2022) - Brzozowski, Jan; Šimić Banović, Ružica; Alpeza, Mirela
ABSTRACT: This article investigates the role of socio-institutional constraints to immigrant entrepreneurship in post-communist countries of the Balkans. The study focuses on Croatia, a country where the immigrant population is still limited, but due to recent EU membership and sustained economic growth, it is expected to increase soon. The article draws upon a qualitative study based on semi-structured interviews with immigrant entrepreneurs and relevant stakeholders (including NGOs and research institutes' representatives). The findings contribute to the mixed embeddedness and institutional theories, as the study demonstrates a growing potential of immigrant entrepreneurship in Croatia, but also persistent barriers connected both with formal and informal institutions in the country. Interestingly, the informal institutions often present even a bigger obstacle for entrepreneurs originating from less developed, non-European countries than the formal ones. This finding indicates a moderating role of social and cultural capital in assessing informal institutions. As the foreign population in Croatia is still very small, immigrants cannot reap the benefits of ethnic concentration and ethnic solidarity. Therefore, for most foreigners in Croatia the embeddedness in immigrant networks of social relations is very limited. Consequently, the shortages in social and cultural capital, combined with a very limited openness towards natives make the access to informal institutions in Croatia very difficult, which in turn discourages entrepreneurial initiatives among immigrants.